INTRACRANIAL COMPLICATIONS OF LUMBAR SPINAL SURGERY - (:unkn) unknown (My University, 2018)
In this study, we present the largest series composed of 10 patients, with different kinds of remote intracranial complications after lumbar spinal surgery. Remote intracranial events happened after lumbar spine surgery that were performed from 2002 to 2017 in senior author’s practice were reviewed and ten patients were retrieved from the database with relevant clinical and radiological information. We have 10 patients (8 women and 2 men; mean age: 56±18.5 years; age range: 12–81 years) with remote intracranial events happened after lumbar spine surgery. Although the presenting symptoms may be mostly nonspecific, remote intracranial event should be suspected in any patient with intractable headach e, focal neurological deficits or unexplained deterioration of consciousness following spine surgery.
Keywords: Cerrahi